UPAYA MENINGKATKAN KETERAMPILAN GERAK DASAR LONCAT HARIMAU DENGAN KARDUS, BOLA DAN TEMAN - Muhammad Aldino; Rahmat Hermawan; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2013)
This study aims to improve basic motor skills tigers jump in class XI IPA-3 MAN Poncowati Terbanggi Large cardboard with the use of tools, balls and friends.  This type of research is a classroom action research (Classroom Action Research). With the research subjects were students of class XI IPA-3, which amounts to 43 students made up of 15 men and 28 women. The instrument used was a basic assessment of the quality movement jump tiger. The results showed that ; 1) in the first cycle with the use of cardboard aids can improve students' basic motion tiger jump, as many as 13 students who completed (30.23%); 2) in the second cycle with the use of tools to improve the motion base ball jump tiger with a mastery level of 48.84%; and 3) in the third cycle with the use of paired with a friend can help improve basic motion jump tiger with a mastery level of 79.07%.  conclusion: With tools such as cardboard boxes, balls and friends can help improve basic motor skills tigers jump in class XI IPA-3 MAN Poncowati Terbanggi Besar.Kata kunci : alat bantu, PTK, loncat harimau, ketuntasan belajar